Hypertension a companion to Braunwald's heart disease - Black, Henry R; Elliott, William J (Elsevier/Saunders, 2013)
Clinical hypertension is one of the most serious long-term problems associated with heart disease. This companion to Braunwald's Heart Disease focuses in depth on this key area of cardiovascular medicine. Complete with practical clinical tools for management, it helps you manage the chronic problems of your hypertensive patients. It covers everything from epidemiology and pathophysiology through diagnosis, risk stratification, treatment, outcome studies, concomitant diseases, special populations and special situations, and future treatments.